2019
DOI: 10.21608/edj.2015.71418
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cortactin and MDM2 in Solid Ameloblastoma and its Malignant Counterpart

Abstract: Ameloblastoma is characterized by heterogeneity regarding its pathogenetic development, molecular abnormalities, and clinical course. Determining the molecular basis underlying these important differences remains challenging. Nevertheless, identifying molecules that influence tumor behavior would be the first steps towards gaining some insights into its pathobiology. MDM2, a 90-95kDa protein coded by a mdm2 gene which is mapped on chromosome 12q13-14. MDM2 is a negative regulator of p53 activity, through bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…N.A., 2019 [19] concluded that MDM2 immunoreactivity was found predominantly in peripheral ameloblast like cells and it was also seen in central stellate reticulum like cells suggesting that peripheral cells essential and mean cell for evaluating the proliferative activity of AM. [18,19,21] As well Kumamoto et al ( 2004) [24] found that elevated expression of MDM2-p53, p14 in benign and malignant AM suggested that alteration of MDM2-p53, p14 cascade leads to oncogenesis or malignant transformation of odontogenic epithelium and is associated also with tissue structuring and cytodifferentiation of AM [24] .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…N.A., 2019 [19] concluded that MDM2 immunoreactivity was found predominantly in peripheral ameloblast like cells and it was also seen in central stellate reticulum like cells suggesting that peripheral cells essential and mean cell for evaluating the proliferative activity of AM. [18,19,21] As well Kumamoto et al ( 2004) [24] found that elevated expression of MDM2-p53, p14 in benign and malignant AM suggested that alteration of MDM2-p53, p14 cascade leads to oncogenesis or malignant transformation of odontogenic epithelium and is associated also with tissue structuring and cytodifferentiation of AM [24] .…”
Section: Discussionmentioning
confidence: 89%
“…Odontogenic tumors are a diverse group of osteo-destructive lesions with a wide range of clinical and biological characteristics. Diagnosis of odontogenic tumors can be challenging due to their rarity and diverse morphology [18][19][20] In view of this fact, a growing number of studies have tried to identify epithelial and mesenchymal factors that participate in the regulation of their growth and determine the differences in behavior between these diseases. The rarity of malignant odontogenic tumors, variations in their pathogenesis and biological behavior all contribute to the difficulty in diagnosing them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations